Development of The ABK-KU Application in Conducting Developmental Assessments in Children with Special Needs - Rafmateti Rafmateti; Fetri Yeni J; Alwen Bentri; Abna Hidayati; Rahmahtrisilvia Rahmahtrisilvia; Risca Amani (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study aims to develop the ABK-KU application as a digital instrument to support practical, accurate, and sustainable assessment of the development of students with special needs. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Subjects in this study consisted of three expert validators, 16 teachers for the practicality test, and 36 teachers for the effectiveness test. Data were analyzed descriptively and quantitatively using percentages and statistical tests of N-Gain Score and Wilcoxon Signed-Rank Test. The results of validation by material, media, and language experts show that this application has a high level of feasibility of 88.85%. The average percentage of practicality assessment of the ABK-KU Application obtained a percentage of 92% in the very practical category. The results of the pretest and posttest obtained the average N-Gain score of 0.8356 (83.56%), while the results of the Wilcoxon signed-rank test showed that Z count was -5.234 and the significance value was 0.001. These results show that ABK-KU is easy to use by teachers and can present child development data in a structured and systematic manner, and provide program recommendations from the assessment results automatically. ABK-KU is worth using as an alternative innovative solution to support the assessment of the development of students with special needs in special schools.